TITLES OF EASTERN RULERS IN THE ANONYMOUS PERSIAN WORK MUJMAL AL-TAWĀRĪKH WA-L-QIṢAṢ - Timohin, Dmitrij Mihajlovic; Tisin, Vladimir Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2026)
The anonymous Persian chronicle dated 1126 CE, known to specialists as the Mujmal al-Tawārīkh wa-l-Qiṣaṣ, contains a highly intriguing section that has remained untranslated into European languages to date. In this section, the anonymous author provides detailed data on the titulature of the rulers of Iran and the “Padishahs of the East,” including mentions of rulers governing territories within the Caucasus and adjacent regions. The origin of various titles or laqabs of the pre-Mongol era continues to be a subject of active scholarly debate. Consequently, the records within the Mujmal al-Tawārīkh wa-l-Qiṣaṣ are of significant value to a wide range of specialists, particularly as the anonymous author presents his own explanatory models for the origins of specific titles. The objective of this study is not only to provide a translation of the specified fragment and accompanying commentary but also to identify potential historiographical links between this portion of the anonymous text and earlier Islamic historical and geographical works. Methodologically, the authors of this article rely on the frameworks of modern comparative source studies. Key findings, in addition to the translation of the relevant section of Mujmal al-Tawārīkh wa-l-Qiṣaṣ, include the author’s specific mention of the rulers of the Alans and Lakz, whose title shah is not applied to other monarchs in this context. While a significant number of the mentioned laqabs are clearly of Turkic origin, the titles of the Alan and Lakz rulers represent a notable exception.